2007
DOI: 10.1097/01.brs.0000257541.91728.a1
|View full text |Cite
|
Sign up to set email alerts
|

Peridural Methylprednisolone and Wound Infiltration With Bupivacaine for Postoperative Pain Control After Posterior Lumbar Spine Surgery

Abstract: Administration of methylprednisolone-bupivacaine provided a favorable effect immediately after posterior lumbosacral spine surgery for discectomy, decompression, and/or spinal fusion without complication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
73
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(76 citation statements)
references
References 26 publications
1
73
1
1
Order By: Relevance
“…This includes the beneficial effect of epidural steroid after lumbar discectomy [18] and from locally applied methylprednisolone in patients undergoing mixed lumbar surgical interventions [19]. The efficacy of glucocorticoids as part of multimodal postoperative pain treatment in different surgical procedures has recently been reviewed [20] demonstrating reductions in both pain scores and morphine consumption.…”
Section: Discussionmentioning
confidence: 99%
“…This includes the beneficial effect of epidural steroid after lumbar discectomy [18] and from locally applied methylprednisolone in patients undergoing mixed lumbar surgical interventions [19]. The efficacy of glucocorticoids as part of multimodal postoperative pain treatment in different surgical procedures has recently been reviewed [20] demonstrating reductions in both pain scores and morphine consumption.…”
Section: Discussionmentioning
confidence: 99%
“…We believe that low doses of methylprednisolone can not produce infection if strict aseptic precautions, meticulous dissection, and prophylactic use of antibiotics are undertaken. Moreover, one report [9] suggested that presence of blood in the epidural space may interfere with the drug action and presence of a vacuum tube drain might lead to inadequate retention of the drug. We used a mini drain after the discectomy in all cases, but we do not think that it can decrease the amount of drug soaked by Gelfoam; instead it will drain the blood from the epidural space and reduce the chance of infection.…”
Section: Discussionmentioning
confidence: 99%
“…Several other reports also suggested the efficacy of local or systemic steroids in the immediate postoperative period. In various studies [6,9,13,14], saline or salinesoaked fat graft or absorbable gel was used in the control group and the effects were recorded. However in clinical practice we never inject saline or saline-soaked fat graft or Gelfoam if we do not intend to apply a local steroid or other agents.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations